Building knowledge of university campus population dynamics to enhance near-to-source sewage surveillance for SARS-CoV-2 detection - Sweetapple, Chris; Melville-Shreeve, Peter; Chen, Albert S.; Grimsley, Jasmine M.S.; Bunce, Joshua T.; Gaze, William; Fielding, Sean; Wade, Matthew J. (The Science of the total environment, 2022)
Wastewater surveillance has been widely implemented for monitoring of SARS-CoV-2 during the global COVID-19 pandemic, and near-to-source monitoring is of particular interest for outbreak management in discrete populations. However, variation in population size poses a challenge to the triggering of public health interventions using wastewater SARS-CoV-2 concentrations. This is especially important for near-to-source sites that are subject to significant daily variability in upstream populations. Focusing on a university campus in England, this study investigates methods to account for variation in upstream populations at a site with highly transient footfall and provides a better understanding of the impact of variable populations on the SARS-CoV-2 trends provided by wastewater-based epidemiology. The potential for complementary data to help direct response activities within the near-to-source population is also explored, and potential concerns arising due to the presence of heavily diluted samples during wet weather are addressed. Using wastewater biomarkers, it is demonstrated that population normalisation can reveal significant differences between days where SARS-CoV-2 concentrations are very similar. Confidence in the trends identified is strongest when samples are collected during dry weather periods; however, wet weather samples can still provide valuable information. It is also shown that building-level occupancy estimates based on complementary data aid identification of potential sources of SARS-CoV-2 and can enable targeted actions to be taken to identify and manage potential sources of pathogen transmission in localised communities. [Display omitted] •Near-to-source wastewater sampling sites are subject to variable upstream populations.•Accounting for population change alters the SARS-CoV-2 trends provided by wastewater-based epidemiology.•Confidence in SARS-CoV-2 trends is strongest when samples are collected during dry weather.•Flush count data can be used to indicate population size and individual building occupancies.•Building-level occupancy estimates aid identification of potential sources of SARS-CoV-2.